Synthesis and Biological Evaluation of Migrastatin Macrotriazoles. Issue 1 (5th December 2016) - Gabba, Adele; Robakiewicz, Stefania; Taciak, Bartłomiej; Ulewicz, Katarzyna; Broggini, Gianluigi; Rastelli, Giulio; Krol, Magadalena; Murphy, Paul V.; Passarella, Daniele
Abstract : The synthesis of three macrotriazoles that are analogues of migrastatin is reported. The synthesis is based on copper(I)‐ and ruthenium‐catalyzed azide–alkyne cycloaddition reactions. The enantiopure terminal alkyne derivatives were prepared by using the Trost desymmetrization, Brown alkoxyallylation and an efficient Colvin reaction. Biological evaluation of the products revealed a promising efficiency in reducing the ability of MDA‐MB‐361 cell lines to migrate. Abstract : Three macrotriazole analogues of the natural product migrastatin were synthesized by using copper(I)‐ or ruthenium‐catalyzed azide–alkyne cycloaddition reactions. The intermediary enantiopure terminal alkynes were synthesized through Trost desymmetrization, Brown alkoxyallylation and efficient Colvin reaction. The compounds were found to reduce the ability of MDA‐MB‐361 cell lines to migrate.